Association Between Iron Status and Risk of Chronic Kidney Disease in Chinese Adults - Zhu, Yongjian; Liu, Xiaozhuan; Li, Ning; Cui, Lingling; Zhang, Xiaofeng; Liu, Xinxin; Yu, Kailun; Chen, Yao; Wan, Zhongxiao; Yu, Zengli (Frontiers in Medicine, 2020)
Background: Even though it is well known that iron deficiency is the result of chronic kidney disease (CKD), whether iron will affect kidney function and disease in the general population is not clear. We thus conducted a nationwide cross-sectional study using data from China Health and Nutrition Survey (CHNS) to assess the relationship of iron status with estimated glomerular filtration rate(eGFR) and CKD among general adults. Methods: A total of 8339 adults from CHNS in the wave of 2009 were included to assess the association between iron status and eGFR/CKD. Serum ferritin(SF), transferrin, soluble transferrin receptor(sTfR), and haemoglobin (Hb) were measured. The relationship of iron status and eGFR was evaluated by using multi-variable linear regression model. The effect of iron status on the odds of CKD was calculated by Logistic regression model. Results: For the association between iron status and eGFR, every 100 ug/L increase in SF was correlated with 0.26 mL/min per 1.73 m² (95%CI: 0.08-0.44) decrease in eGFR, every 5 g/L increase in sTfR was associated with a decrease of 6.00 mL/min per 1.73 m² (95%CI: 3.79-8.21) in eGFR. There were no significant associations between Hb or transferrin with eGFR. For the association between iron status and CKD, every 5 g/L increase in sTfR was associated with an OR of 3.72 (95% CI: 2.16-6.13) for CKD. The concentrations of Hb were associated with the odds of CKD in a U-shaped manner, with the lowest risk in the Hb range of 136-141g/L. There was a positive correlation between SF concentration and CKD prevalence but not in a dose–response manner. The odds of CKD for participants in the highest tertile increased by 28% (98% CI: 1%-63%) compared with those in the lowest tertile. Conclusion: The concentration of SF and sTfR were positively correlated with the odds of CKD, and Hb was associated with the odds of CKD in a U-shaped manner. Further large prospective researches are warranted to confirm these findings.